RFID for dummies - Sweeney, Patrick J., II (--For dummies., 2005)
Many companies have asked suppliers to begin using RFID (radio frequency identification) tags by 2006. R.F.I.D. allows pallets and products to be scanned at a greater distance and with less effort than barcode scanning, offering superior supply-chain management efficiencies. This unique plain-English resource explains R.F.I.D. and shows C.I.O.s, warehouse managers and supply-chain managers how to implement R.F.I.D. tagging in products and deploy R.F.I.D. scanning at a warehouse or distribution center. It also covers the business case for R.F.I.D., pilot programs, timelines and strategies for site assessments and deployments, testing guidelines, privacy and regulatory issues and more.